Physical and Performance Characteristics of 3×3 Professional Male Basketball Players - Dimitrije Cabarkapa; Darko Krsman; Damjana V. Cabarkapa; Nicolas M. Philipp; Andrew C. Fry (MDPI AG, 2023)
Despite exponential growth in popularity over the last decade and recently becoming an Olympic sport, the amount of scientific literature focused on depicting a profile of successful 3×3 basketball players is sparse. Thus, the purpose of this study was to present the physical and performance characteristics of professional 3×3 male basketball players and how they differ between elite and non-elite athletes. The anthropometrics, vertical jump, agility, and sprint performance parameters collected from ten players during regular training sessions were (<semantics><mover>x¯</mover></semantics> ± SD): height (193.7 ± 4.5 cm), weight (89.2 ± 4.1 cm), wingspan (196.5 ± 5.2 cm), squat jump (43.5 ± 4.6 cm), countermovement jump with (53.3 ± 4.4 cm) and without an arm swing (46.3 ± 4.0 cm), reactive strength index (2.4 ± 0.3 m/s), t-test (10.3 ± 0.3 s), 505 drill (2.4 ± 0.2 s), 10 m sprint (1.5 ± 0.1 s), 30 m sprint (4.0 ± 0.3 s), shuttle run (27.7 ± 1.7 s), and bench press (98.2 ± 10.0 kg) and back squat (139.5 ± 17.6 kg) one repetition maximum. Additionally, the average and maximal heart rate (HR) responses during simulated games were 160.6 ± 8.0 and 188.5 ± 6.3 bpm, with players spending 6.3 ± 4.2, 11.4 ± 5.2, 13.9 ± 3.5, 26.4 ± 10.4, and 42.1 ± 10.0% of the total time in HR Zones 1-5, respectively. Interestingly, no statistically significant differences in the aforementioned physical and performance parameters were noted between elite and non-elite players. Overall, the findings of the present study provide coaches, sports scientists, and strength and conditioning practitioners with information that can aid in the athlete selection process, detection of areas for further improvement, and development of training regimens that resemble 3×3 basketball on-court competitive demands.